Ep058 about storytelling and the Tomboy Survival Guide. - Jarvis, Dale (2016)
Ivan Coyote is the award-winning author of ten books, the creator of four short films, and has released three albums that combine storytelling with music. Ivan is a seasoned stage performer and long-time road dog, and over the last eighteen years has become an audience favourite at storytelling, writer's, film, poetry, and folk music festivals from Anchorage to Amsterdam. Ivan's 11th book, Tomboy Survival Guide, was released in the fall of 2016 with Arsenal Pulp Press. In this podcast, we discuss the writing process, performing, Ivan’s new book Tomboy Survival Guide, trans and queer stories shared after Ivan’s performances, and their latest projects.